HUBUNGAN USIA IBU DENGAN KEJADIAN PRE â EKLAMSI PADA IBU HAMIL DI RSUD KODYA SEMARANGTAHUN 2008 - Sri Wahyuning, Taryunah, Rinayati, (STIKES Widya Husada Semarang, 2010)
Mortality of high pregnant mother in Indonesia, one of it`s cause is pre eklamsi. Pre-Eklamsi there is relation with age, in RSUD Kodya Semarang of year 2008 there are 40 mother of pregnancy experiencing of Pre-Eklamsi. Intention of this research to know relation/link of age of mother with occurence of Pre-Eklamsi of at pregnant mother in RSUD Kodya Semarang of year 2008. Method used by is study of correlation with approach of study restropektif. Population as much 40 people. Sample used by is totalizeing to from other side. use of Data use data of sekunder by filling cek-list. Analyse relation/link 2 variable use chi-square with level of significan 5 %. Result of research show most mother of pregnancy experiencing of pre-eklamsi of group of age which have risk < 20 and > 35 year ) as much 22 responder ( 55 ) and pursuant to test of stastitic of where counting/calculating = 47,763 > tables of = 3,841, by level is signifikan 5% and dk = 1, Value of correlation coefficient show Is ha accepted and Ho refused. Becoming there is relation/link of age of mother with occurence of pre-eklamsi of pregnant mother in RSUD Kodya Semarang of year 2008. Â Keyword : Mother Age, pre-eklamsi